Affect, risk and local politics of knowledge: changing land use in Narrabri, NSW. Issue 4 (2nd October 2018) - Threadgold, Steven; Farrugia, David; Askland, Hedda; Askew, Michael; Hanley, Jo; Sherval, Meg; Coffey, Julia
ABSTRACT: As conflicts emerge over land use when extractive industries arrive, what counts as legitimate knowledge about the risks generated by these developments becomes important to how individuals formulate their opinions. This article analyses knowledge, risk and perceptions of future land use in the Narrabri Shire, a rural area in Australia. In a risk society, especially a 'post-truth' one, the production of knowledge, whether scientific, political, media or commercially driven, does not provide more security and certainty, but more insecurity and uncertainty. This article uses Bourdieusian concepts informed with theoretical insights about affect and emotion to understand how reflexivity about risks and environmental politics are interpreted. Land use practices are emotional for some local farmers, where their 'sense of one's place' is structured by their deep connection with the land and is therefore structuring of their land use politics. For others, their response may be couched as more economically 'rational', but this also expresses an emotional position in an affective economy that destabilises traditional economic understandings of rational/emotional dichotomies. Affect and illusio can contribute to understanding the colour and intensity of the positions occupied in response to land use disputes.